Protecting Benzylic CH Bonds by Deuteration Doubles the Operational Lifetime of Deep‐Blue Ir‐Phenylimidazole Dopants in Phosphorescent OLEDs (Advanced Optical Materials 16/2021). Issue 16 (18th August 2021) - Bae, Hye Jin; Kim, Jong Soo; Yakubovich, Alexander; Jeong, Jinhoon; Park, Sangho; Chwae, Jun; Ishibe, Satoko; Jung, Yongsik; Rai, Virendra Kumar; Son, Won‐Joon; Kim, Sunghan; Choi, Hyeonho; et al.
Abstract : The kinetic isotope effect (KIE) can be used to improve the operational lifetime by stabilizing a series of blue Ir‐dopants in phosphorescent OLED devices (see article number 2100630 by Hye Jin Bae and co‐workers). Deuterating the vulnerable benzylic C–H bonds, which are proposed to participate in the degradative reaction, allows for taking advantage of the innately slower C–D cleavage reaction rate to protect the Ir‐dopants. The deuterium incorporation targeting the most vulnerable C–H bonds is a viable strategy to significantly increase the operational lifetime.